2015
DOI: 10.1016/j.alcohol.2014.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Assessing ethanol's actions in the suprachiasmatic circadian clock using in vivo and in vitro approaches

Abstract: Research over the past decade has demonstrated substantial interactions between the circadian system and the processes through which alcohol affects behavior and physiology. Here we summarize the results of our collaborative efforts focused on this intersection. Using a combination of in vivo and in vitro approaches, we have shown that ethanol affects many aspects of the mammalian circadian system, both acutely as well as after chronic administration. Conversely, we have shown circadian influences on ethanol c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 165 publications
(222 reference statements)
1
13
0
Order By: Relevance
“…Much effort has gone into determining whether alcohol affects the SCN using various in vivo and in vitro approaches (Prosser and Glass, 2014). Previous studies suggested that chronic alcohol had little effect on the ability of the SCN to entrain to external L:D cycles (Brager et al, 2010), consistent with our results that rats exhibited robust 24-hour periodicities in temperature and activity under a 12:12 L:D cycle.…”
Section: Discussionsupporting
confidence: 88%
“…Much effort has gone into determining whether alcohol affects the SCN using various in vivo and in vitro approaches (Prosser and Glass, 2014). Previous studies suggested that chronic alcohol had little effect on the ability of the SCN to entrain to external L:D cycles (Brager et al, 2010), consistent with our results that rats exhibited robust 24-hour periodicities in temperature and activity under a 12:12 L:D cycle.…”
Section: Discussionsupporting
confidence: 88%
“…Chronic alcohol consumption could possibly impact the master clock in the SCN (Prosser & Glass, 2014), thereby altering feeding and locomotor activity rhythms. For example, in rats a year-long alcohol exposure resulted in the depression of key SCN neuropeptides (Madeira et al, 1997), and a 2-week alcohol liquid diet altered the SCN rhythmic expression profiles of the clock genes per2 and per3 (Chen, Kuhn, Advis, & Sarkar, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, chronic alcohol-induced body temperature change and fragmented sleeping patterns appear to shift behaviors, which likely contribute to the phase shift in the hepatic clock. Interestingly, the clock genes per1 , per2, and NPAS2 , that exhibit altered expression patterns in the steatotic liver under CAF (Zhou et al, 2014), have also been shown to contribute to the regulation of behaviors associated with feeding or alcohol preference: per2 mutant mice exhibit enhanced alcohol preference/intake (Spanagel et al, 2005), including increased free-choice ethanol drinking bouts during both the dark and light phases of the LD cycle (Prosser & Glass, 2014); per1 mutant mice display an altered feeding rhythm (Liu et al, 2014); and NPAS2 null mice exhibit delayed anticipatory locomotor activity in response to restricted feeding (Dudley et al, 2003). Lastly, a dampened plasma cortisol rhythmicity has been reported in chronic-alcohol liver disease patients (Rosman et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol can modulate the phase shifting effects of photic and non-photic stimuli (for a review see Prosser and Glass, 2015), although chronic consumption of ethanol in a light-dark cycle does not alter the phase of the circadian pacemaker in the SCN (Filiano et al, 2013). In hamsters, systemic administration of ethanol attenuates light-induced phase advances without affecting phase delays (Seggio et al, 2007; Ruby et al, 2009a, 2009b).…”
Section: Modulation Of Gaba Neurotransmissionmentioning
confidence: 99%